A two‐CpG‐based prognostic signature for oral squamous cell carcinoma overall survival. Issue 6 (12th December 2018) - Chen, Yanping; Hei, Naiheng; Zhao, Jianguang; Peng, Shixiong; Yang, Kaicheng; Chen, He; Cui, Zifeng; Jin, Linyu; Sun, Ran; Guo, Jingxin
Abstract: Oral squamous cell carcinoma (OSCC) represents one of the most common head and neck cancer that with dire prognosis due partly to the lack of reliable prognostic biomarker. Here, we aimed to develop a CpG site–based prognostic signature through which we could accurately predict overall survival (OS) of patients with OSCC. We obtained OSCC‐related DNA methylation and gene expression data sets from the public accessible Gene Expression Omnibus. Correlations between methylation level of CpG sites and OS of patients with OSCC were assessed by univariate Cox regression analysis followed by robust likelihood‐based survival analysis on those CpG sites with permutation P < 0.05 for further screening the optimal CpG sites for OSCC OS prediction based on the risk score formula that composed of the methylation level of optimal CpG sites weighted by their regression coefficients. Besides, differential expression genes (DEGs) and differential methylation genes (DMGs) in OSCC samples compared with normal samples were obtained and shared genes were considered as vital genes in OSCC tumorgenesis and progression. As a result, two CpG sites including cg17892178 and cg17378966 that located in NID2 and IDO1, respectively, were identified as the optimal prognostic signatures for OSCC OS. In addition, 12 overlapping genes between DEGs and DMGs that closely associated with inflammation or blood and tissue development–related biological processes were obtained. In conclusions, this study should provide valuable signatures for OSCC diagnosis and treatment. Abstract : We obtained a two‐CpG‐based signature through which we could predict oral squamous cell carcinoma (OSCC) prognosis. A total of 12 genes including AIM2, BST2, CA3 and so on, may be vital for OSCC tumorigenesis and progression.